ULTRASOUND -A USEFUL COMPLEMENTARY TOOL TO MAMMOGRAPHY IN ASSESSMENT OF SYMPTOMATIC BREAST DISEASES - Fatima, Syeda Tatheer; Zahur, Zainab; Jeilani, Asif; Hussain, Syed Jawad Akhtar; Abbasi, Nadeem Zia; Khan, Amjad Aziz; Khan, Kamran; Sheikh, Abdul Samad; Ali, Furqan; Memon, Khalid Hussain (Journal of Ayub Medical College Abbottabad, 2015)
Background: Breast cancer is the most common female malignancy worldwide. Pakistan has the highest incidence rate of breast cancer than any other Asian population. The purpose of the study was to evaluate the worth of sono-mammography in diagnosis of symptomatic breast diseases by comparing it with mammogram. Methods: In this cross-sectional validation study, 45 subjects with mean age of 45±12.07 were included. Majority of the patients presented with complaint of breast lump. After complete history and clinical examination, all the patients had high resolution ultrasound of bilateral breasts and axilla followed by bilateral mammography. Histopathology was taken as gold standard in this study. The exclusion criteria were pregnancy and patients having direct clinical signs of breast malignancy. Results: Based on histopathology, out of 45 patients with breast symptoms, 12 patients had benign lesions, whereas 32 patients were diagnosed as the cases of breast cancers. Finally one patient did not have biopsy proven final diagnosis. Sensitivity and specificity of ultrasound were calculated to be 100% and 67% as compared to sensitivity and specificity of 90.6% and 91.7% for that of mammography. Conclusions: Ultrasound is a useful complementary tool to mammography in assessment of symptomatic breast diseases since it helps in characterization and localization of breast lesions seen on mammogram and it is not limited by dense breasts. Also it should be the considered as initial imaging technique for assessment of palpable breast lumps. Keywords: Breast cancer, Mammogram, Ultrasound.